N6‐methyladenosine and RNA secondary structure affect transcript stability and protein abundance during systemic salt stress in Arabidopsis. (24th July 2020) - Kramer, Marianne C.; Janssen, Kevin A.; Palos, Kyle; Nelson, Andrew D. L.; Vandivier, Lee E.; Garcia, Benjamin A.; Lyons, Eric; Beilstein, Mark A.; Gregory, Brian D.
Abstract: After transcription, a messenger RNA (mRNA) is further post‐transcriptionally regulated by several features including RNA secondary structure and covalent RNA modifications (specifically N 6 ‐methyladenosine, m 6 A). Both RNA secondary structure and m 6 A have been demonstrated to regulate mRNA stability and translation and have been independently linked to plant responses to soil salinity levels. However, the effect of m 6 A on regulating RNA secondary structure and the combinatorial interplay between these two RNA features during salt stress response has yet to be studied. Here, we globally identify RNA‐protein interactions and RNA secondary structure during systemic salt stress. This analysis reveals that RNA secondary structure changes significantly during salt stress, and that it is independent of global changes in RNA‐protein interactions. Conversely, we find that m 6 A is anti‐correlated with RNA secondary structure in a condition‐dependent manner, with salt‐specific m 6 A correlated with a decrease in mRNA secondary structure during salt stress. Taken together, we suggest that salt‐specific m 6 A deposition and the associated loss of RNA secondary structure results in increases in mRNA stability for transcripts encoding abiotic stress response proteins and ultimately increases in protein levels from these stabilized transcripts. In total, our comprehensive analyses reveal important post‐transcriptional regulatory mechanisms involved in plant long‐term salt stress response and adaptation.